APPLICATION OF HEAT-INSULATING COMPOSITE GYPSUM FOR ENERGY-EFFICIENT CONSTRUCTION - Adxamjon Khamidov, Islombek Akhmedov, Yusupov Shavkat, Zayniddin Jalalov, Isroiljon Umarov, Sodiqjon Xakimov, Kazadayev Aleksandr (Journals Park Publishing, 2022)
The article deals with the use of finishing slabs from gypsum heat-insulating composite materials based on industrial waste in energy-efficient construction, the compositions and properties of these materials are considered.
Keywords: Construction, energy efficiency, finishing boards, thermal insulation materials, gypsum, travertine, properties.